A traffic shaping optimization methodology for web systems - Mesquita, Caio; Cavalca, Ulisses; Pereira, Adriano César Machado; Carrano, Eduardo G. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2013)
In recent years, computer networks have been characterized by heterogeneous traffic and dynamic management of different kinds of services. The web and network requirements have increased within time and, since bandwidth is limited, it becomes necessary to employ optimization procedures in order to make the network able to operate in its full capacity. Traffic shaping mechanisms implement Quality of Service (QoS) concepts to ensure acceptable service levels. This paper describes an approach for traffic shaping optimization. It is proposed a methodology based on throughput and packet loss optimization using genetic algorithms. This method was validated using actual data from a network infrastructure of a Public Educational Institution.